2012
DOI: 10.1016/j.drugalcdep.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of two randomized trials of bupropion for methamphetamine dependence: Suggested guidelines for treatment discontinuation/augmentation

Abstract: Background Two clinical trials have shown efficacy for bupropion in treating methamphetamine (MA) dependence among those with moderate baseline MA use. However, treatment response is highly variable and it is unclear what duration of treatment is necessary to determine if maintaining the treatment course is indicated or if discontinuation or augmentation is appropriate. The present study assessed the relationship among early bupropion treatment response for moderate MA users and end-of-treatment (EOT) abstinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…We recently examined moderate users of methamphetamine from two clinical trials of bupropion – a subgroup in which the medication has demonstrated preliminary efficacy. Results were consistent with the findings reported here suggesting the possibility that immediate responsiveness may be critically important for a range of addiction treatments (Brensilver, Heinzerling, Swanson, & Shoptaw, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…We recently examined moderate users of methamphetamine from two clinical trials of bupropion – a subgroup in which the medication has demonstrated preliminary efficacy. Results were consistent with the findings reported here suggesting the possibility that immediate responsiveness may be critically important for a range of addiction treatments (Brensilver, Heinzerling, Swanson, & Shoptaw, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…However, the present study included MA users seeking to stop or reduce MA use and a larger sample size, and participants were monitored for MA use as opposed to psychological measures of reinforcement. Furthermore, our data appear to support the conclusions of Brensilver et al (2012), whose retrospective analyses of other bupropion research (Elkashef et al, 2008 and Shoptaw et al, 2008) suggest that treatment response can be predicted after two to three weeks (Figure 2); responders and non-responders in this study appeared to diverge in terms of MA-negative UDS by week 3.…”
Section: Discussionsupporting
confidence: 85%
“…A retrospective analysis of these two studies suggested that bupropion may be effective in patients with only moderate baseline methamphetamine use. Thereby, the failure to provide at least two negative urine samples in the first three weekly tests would confer an enhanced risk of treatment failure (Brensilver, Heinzerling, Swanson, & Shoptaw, 2012). However, abstinence was significantly higher in those individuals with high medication adherence compared to those with low adherence in a patient population with low methamphetamine abuse (Heinzerling et al, 2014).…”
Section: Bupropionmentioning
confidence: 99%